Personal Data Protection Strategies in the Digital Business Era: A Normative and Empirical Juridical Analysis of the Personal Data Protection Law - Augustinus Lumban Tobing; Nanda Dwi Rizkia (Eduvest - Journal of Universal Studies, 2026)
The development of digital businesses in Indonesia is driving an increase in personal data-based transactions that require a strong and integrated protection system. This study aims to identify personal data protection strategies through literature analysis that includes aspects of regulation, organizational governance, technology, and digital literacy. Using a literature review approach to 20 articles from the Scopus, Google Scholar, DOAJ, and SINTA databases, this study analyzes four main stages: identification, selection, thematic analysis, and theoretical synthesis. The results of the analysis show five main themes in personal data protection, namely regulation and legal compliance, the implementation of Privacy by Design and Security by Design, organizational governance and risk management, digital literacy and human factors, as well as implementation challenges and best practices. The effectiveness of data protection is highly dependent on regulatory compliance, the implementation of Privacy by Design, public privacy awareness, and adaptive organizational governance. Regulations such as GDPR, CCPA, and the Indonesian PDP Law provide a comprehensive legal framework, but their effectiveness is determined by the ability of institutions and businesses to translate legal norms into sustainable operational practices. This study recommends strengthening synergy between public policies, industry, and society in building a sustainable data protection culture.